PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENYIAPKAN KESEHATAN MENTAL SISWA SMA ABDUL WAHID HASYIM TEBUIRENG JOMBANG - Abdurrochim Abdurrochim; Sholihul Anshori (JURNAL ILMIAH NUSANTARA, 2024)
The role of an Islamic Religious Education teacher is someone who is responsible for the development of students who can develop their achievements to have strength in religious understanding and noble morals. Mental health is an expression of students through all actions and knowledge with the aim of developing themselves according to their potential, talents and interests.The focus of the problem in this research is: 1). What is the role of Islamic Religious Education teachers in preparing students' mental health at SMA Abdul Wahid Hasyim Tebuireng Jombang, 2). What are the supporting and inhibiting factors for the role of Islamic Religious Education teachers in preparing students' mental health at SMA Abdul Wahid Hasyim Tebuireng Jombang. The results of the research show that the role of Islamic Religious Education teachers in preparing students' mental health at SMA Abdul Wahid Hasyim Tebuireng Jombang is: 1). The role of the Islamic Religious Education teacher at SMA Abdul Wahid Hasyim Tebuireng Jombang is that the teacher has a responsibility and role towards his students to educate, direct, develop and evaluate students so that they have moral character with good moral character. The role of Islamic Religious Education teachers in preparing students' mental health at Abdul Wahid Hasyim Tebuireng Jombang High School is that teachers educate their students and direct their students to always have mental and spiritual health which will transform them into students who have sufficient mental health. 2). The supporting and inhibiting factors for the role of Islamic Religious Education teachers in preparing students' mental health at Abdul Wahid Hasyim Tebuireng Jombang High School are through examples that can be seen, namely looking at the character of the teacher himself, how the teacher behaves, conveys things, conveys his opinions, and the way he communicates with his students.